Counter-Radicalization through Problem Based Learning in the Perspective of the Al Qur'an - Sarnoto, Ahmad Zain; Burhanuddin, Nandang (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2021)
This study departs from the problem of the increasing violence of movements in the name of religion in the world of education, especially schools and pesantren. The perpetrators were not only students but also teachers and those closest to the students. Infiltration is not only in face-to-face